Inflation and Economic Growth in Zimbabwe is there Any Inflation Threshold Level? - Runganga, Raynold (International Journal of Applied Economics, Finance and Accounting, 2020)
This study examines the existence of threshold level as well as the relation between inflation and economic growth in Zimbabwe using annual data for the period 1981 to 2018. While the Dynamic Ordinary Least Squares (DOLS) shows that inflation has a negative impact on economic growth and the share of gross capital formation in gross domestic product has positive impact on economic growth, Engle-Granger test shows that there is long-run relationship between the variables. The conditional least squares shows that there is a non-linear relationship between inflation and economic growth. The threshold level of inflation above which additional increase in inflation slows economic growth is 4 per cent. Inflation below the threshold level of 4 per cent has significant positive impact on economic growth but this effect turns out to be negative when inflation rise above the threshold level of inflation. The findings also show that low inflation has a positive impact on economic growth. The study results imply that policy makers should ensure that inflation is kept below the threshold level of 4 per cent and this should be the inflation target in order to achieve higher economic growth.